SCIENTIFIC-POLITICAL POPULISM AS A «NEW INQUISITOR»: WITCH HUNTS IN THE TWENTY-FIRST CENTURY - Andrieieva, Olha (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2026)
The article analyzes the phenomenon of scientific-political populism as one of the most dangerous transformations of contemporary populism in the twenty-first century. It demonstrates that, under current conditions, populism transcends classical ideological divisions and functions as a political-discursive technology aimed at reducing the complexity of social reality and mobilizing society through moral dichotomization. The attention is paid to science-related populism as a form of delegitimization of expert and academic knowledge, manifested in the symbolic construction of an image of the «internal enemy» among scholars, experts, and intellectual minorities.Employing the metaphor of the «new inquisitor», the author conceptualizes contemporary witch-hunt practices not as a historical anachronism but as a recurrent socio-political mechanism of response to systemic crises, security uncertainty, and radical structural transformations. The article demonstrates historical continuity and identifies three stages of witch hunts which, despite differences in targeted groups and mechanisms, retain a common logic of moral exclusion and control over the truth.Special attention is devoted to the Ukrainian case in the context of the full-scale war of Russian Federation against Ukraine. It is argued that the combination of postcolonial experience, the accumulated trauma of the 2014–2022 war period, and the existential threat that emerged after 2022 has created a specific environment of heightened security vigilance in which the risk of transforming rational security practices into a witch-hunt logic increases significantly. The article demonstrates that, in this context, science-related populism undermines democratic institutions, academic freedoms, and informational resilience, while simultaneously serving as an instrument of short-term political mobilization. The study concludes that recognizing the boundaries between security imperatives and populist moral mobilization is critically important for preserving science as a core element of national security.